The Influence of Electronic Word of Mouth on Purchase Intention of Compass Shoe Customers in Padang City with Brand Image as a Mediating Variable - Alfajri , Salman; Thaib , Ilham (CV. ITTC INDONESIA, 2024)
The aim of this research is to analyze: (1) The influence of E-WOM on Purchase Intention for Compass Shoes in Padang City. (2) The influence of E-WOM on the Brand Image of Compass Shoes in Padang City. (3) Influence of Brand Image on Purchase Intention for Compass Shoes in Padang City. 4) Influence of E-WOM on Purchase Intention for Compass Shoes in Padang City with Brand Image as a mediating variable. The type of data in this research is quantitative, the data source is primary data through distributing questionnaires via Google Form, the sampling technique is purposive sampling technique, the data analysis tool is SEM analysis using the Smart PLS VERSION 4 application. Research Results: (1) There is a significant influence between E-WOM on Purchase Intention for Compass Shoes in Padang City. 2) There is a significant influence between E-WOM on the Brand Image of Compass Shoes in Padang City. 3) There is a significant influence between Brand Image on Purchase Intention for Compass Shoes in Padang City. 4) There is a significant influence between E-WOM on Purchase Intention for Compass Shoes in Padang City through brand image